2006
DOI: 10.1111/j.1469-8137.2006.01791.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of fungal genes at preinfection and mycorrhiza establishment between Terfezia boudieri isolates and Cistus incanus hairy root clones

Abstract: Summary• Changes in gene expression by isolates of Terfezia boudieri during mycorrhization with Cistus incanus hairy roots were followed.• Four fungus-hairy root clone combinations were cultivated under two sets of conditions, in which the root and the fungus were separated by a cellophane sheet or were allowed physical contact. One of the combinations produced endomycorrhizas, the other three solely ectomycorrhizas. Fragments isolated by cDNA-AFLP analysis from cellophane-separated cultures (preinfection) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Genes involved in fungal cell division and proliferation, differentiation and signaling, synthesis of cell wall and extracellular matrix, plant defense or stress response, and primary metabolism appeared to be specifically up-regulated in mycorrhizas (Martin et al, 2007). Similar large-scale gene expression analyses have been conducted in the ectomycorrhizal ascomycetes Terfezia boudieri (Zaretsky et al, 2006) and in the whitish truffle Tuber borchii (Lacourt et al, 2002;Gabella et al, 2005;Montanini et al, 2006a). In the case of T. borchii, nitrogen starvation, an abiotic stress that accompanies (and perhaps contributes to) symbiosis establishment, was used to identify changes in gene expression in stages immediately before mycorrhiza formation.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Genes involved in fungal cell division and proliferation, differentiation and signaling, synthesis of cell wall and extracellular matrix, plant defense or stress response, and primary metabolism appeared to be specifically up-regulated in mycorrhizas (Martin et al, 2007). Similar large-scale gene expression analyses have been conducted in the ectomycorrhizal ascomycetes Terfezia boudieri (Zaretsky et al, 2006) and in the whitish truffle Tuber borchii (Lacourt et al, 2002;Gabella et al, 2005;Montanini et al, 2006a). In the case of T. borchii, nitrogen starvation, an abiotic stress that accompanies (and perhaps contributes to) symbiosis establishment, was used to identify changes in gene expression in stages immediately before mycorrhiza formation.…”
Section: Introductionmentioning
confidence: 55%
“…, 2007). Similar large‐scale gene expression analyses have been conducted in the ectomycorrhizal ascomycetes Terfezia boudieri (Zaretsky et al. , 2006) and in the whitish truffle Tuber borchii (Lacourt et al.…”
Section: Introductionmentioning
confidence: 83%
“…Such explorations have been undertaken at two expression levels, that of mRNA (in the form of cDNA) (Voiblet et al 2001;Podila et al 2002;Sundaram et al 2004) and that of protein (Hilbert et al 1991;Burgess et al 1995;Tarkka et al 1998). Whatever the method of study, however, very little work has been done on gene expression changes during the establishement of mycorrhizas by truffles (Pierlioni et al 2001;Polidori et al 2002;Menotta et al 2004;Miozzi et al 2005), and only a single study directed at desert truffles (Zaretsky et al 2006b) has been reported which will be discussed below. Previously, tracking of gene expression changes corresponding to ecto-and endomycorrhizal establishment could not be undertaken due to the lack of suitable study systems.…”
Section: Genes Expressed In Fungus and Plant Prior To And Under Mycormentioning
confidence: 96%
“…The latter exhibited altered expression patterns with respect to preinfection and mycorrizal conditions (Zaretsky et al 2006b). …”
Section: Genes Expressed In Fungus and Plant Prior To And Under Mycormentioning
confidence: 96%
See 1 more Smart Citation